Pengembangan E-Promosi Songket Minangkabau untuk Optimalisasi Pemasaran UMKM di Kecamatan IV Koto - Putri, Putri; Annas, Firdaus; Koto, Nurul Aini (JOVISHE : Journal of Visionary Sharia Economy, 2023)
The development of Minangkabau songket e-promotion based on OpenCart aims to improve the effectiveness of marketing of Micro, Small, and Medium Enterprises (MSMEs) in IV Koto District. Minangkabau songket is one of the cultural products that has high artistic value and is full of local traditions, but until now it is still not well known in the wider market, both nationally and internationally. This problem is caused by limited market access and minimal use of digital technology in marketing songket products by MSME actors. Therefore, the application of information technology, especially in the form of OpenCart-based e-promotion, is an important strategy to introduce and market local products. This study uses a system development method with an Agile approach. This approach includes several main stages, namely needs analysis to understand the constraints and needs of MSMEs, user-friendly interface design, development of a system based on the OpenCart platform, and testing of e-promotion applications to ensure functionality and convenience. The results of the study show that the OpenCart-based e-promotion system is able to expand the marketing reach of Minangkabau songket products, increase product visibility in the digital world, and make it easier for consumers to access and purchase these products. In addition, this platform also allows MSMEs to manage sales independently, from product offerings to transaction management. This provides significant convenience and efficiency, while increasing the competitiveness of MSMEs in an increasingly competitive market.